Gender Violence and the Transnational Politics of the Honor Crime - Olwan, Dana M. (The Ohio State University Press, 2021)
In Gender Violence and the Transnational Politics of the Honor Crime, Dana M. Olwan examines how certain forms of violence become known, recognized, and contested across multiple geopolitical contexts-looking specifically at a particular form of gender-based violence known as the "honor crime" and tracing how a range of legal, political, and literary texts inform normative and critical understandings of this term. Although studies now acknowledge the complicated mobilizations of honor crime discourses, the ways in which these discourses move across different geographies and contexts remain relatively unexplored. This book fills that void by providing a transnational feminist examination of the disparate yet interconnected sites of the US, Canada, Jordan, and Palestine, showing how the concept travels across nations and is deployed to promote hegemonic agendas.